A biogeographic and evolutionary analysis of the flora of the North-eastern cerrado, Brazil. (3rd September 2019) - Vieira, Leandro T. A.; Castro, Antonio A. J. F.; Coutinho, Joxleide M. C. P.; de Sousa, Samara R.; de Farias, Ruth R. S.; Castro, Nívea M. C. F.; Martins, Fernando R.
ABSTRACT: Background : The forest-savanna habitat switching is thought to have been a recurrent event in evolutionary history. Notwithstanding, the centre of the Cerrado, a large biogeographic domain, may be hypothesised to be a region with historical climatic stability and thus is predicted to contain high richness of cerrado species and the presence of few species from adjacents domains. Aims : We tested if today's flora of the north-eastern cerrado (NC), a peripheral province of the domain, demonstrated an observable gradient in their distribution from centre of the Cerrado towards adjacents domains. Methods : We compiled vegetation survey data for 178 sites in the cerrado of north-eastern Brazil. Distribution patterns of plant taxa were assessed using multivariate techniques. Results : We recorded 1071 species in 390 genera and 85 families. Almost 40% were monogeneric families and ca. 50% were monospecific genera. The species composition in the NC followed a gradient related to the distance from the centre of the Cerrado towards its periphery. Conclusions : We show that the NC flora is unique and much richer than previously thought and that it is likely to be an outcome of evolutionary processes and of today's intermixing of species from adjacent formations.